PEMETAAN POTENSI PENINGGALAN KOLONIAL DI KEMUKIMAN SAREE (KECAMATAN LEMBAH SEULAWAH, ACEH BESAR) - Oktaviana, Dina Oktaviana; Rizky, Sarvina Fitri (Jurnal Arsitektur ZONASI, 2023)
Aceh Besar Regency is one of the areas that was colonized by the Dutch colonialists. Evidence of the arrival of the invaders found various buildings and infrastructure made. One of them is the discovery of a former railroad track that connects Padang Tiji (Pidie) to Gampong Lamtamot (Aceh Besar). In addition, buildings in the form of chimneys, houses, wells, ponds, old dams, and water distribution tanks were found in the Saree Settlement, Lembah Seulawah District. The abandoned building can now be used as a historical tourist spot which the Greater Aceh Region has also fought for for Indonesian independence. This research was conducted to map each heritage in the Saree Settlement and help explore the potential of each heritage. To facilitate the process of obtaining results, the method used in this study is a qualitative analysis method by displaying the points of colonial heritage locations. The data collected is the result of direct observation, interviews, and secondary data. The results of observations that have been made at several heritage sites, there are still buildings that are not well maintained and there are also some buildings that have been treated and have even been used as tourist attractions. Furthermore, parties that can support the implementation of areas that will be used as tourist attractions also pay attention to local wisdom and help improve to economic of the surrounding community. By inviting and fostering small communities so that their standard of living is guaranteed and decent.